THE ROLE OF TEACHER‑CENTERED AND STUDENT‑CENTERED APPROACHES IN EFFECTIVE TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article investigates the theoretical foundations, practical implementations, and relative strengths and limitations of teacher‑centered and student‑centered instructional approaches in education. Drawing on a wide range of scholarly research across disciplines — including language learning, science education, and general pedagogy — this study illustrates how each model impacts cognitive development, learner engagement, academic performance, and classroom dynamics. Beyond theoretical exposition, the article offers empirical evidence and classroom‑based examples, arguing that a contextualized and balanced integration of both approaches is essential for addressing diverse learner needs in contemporary educational settings. This integrated approach aligns with global educational frameworks advocating for 21st‑century skills and adaptable pedagogy.